Potensi Seduhan Limbah Baglog Jamur Tiram (Pleurotus ostreatus) dalam Menekan Populasi Radopholus similis dan Meloidogyne spp. pada Tanah Asal Perakaran Tanaman Lada (Piper nigrum L) - PRADANA, ANKARDIANSYAH PANDU; PUTRI, DIANA; MUNIF, ABDUL (Jurnal Sumberdaya Hayati, 2017)
Indonesia is one of the largest pepper producing countries in the world. One of the pepper-producing provinces in Indonesia is the Bangka Belitung Islands (Babel). However, the infection of Radopholus similis and Meloidogyne spp. which causes yellow disease becomes one of obstacles in pepper cultivation in Babel. Thus, alternative solution to overcome this yellow disease is by reducing the amount of nematode inoculum of R. similis and Meloidogyne spp. in soil. This study aimed to determine the effectiveness of the infusion of oyster mushrooms baglog waste enriched with molasses to control the population of R. similis and Meloidogyne spp. and to increase the population of rhizobacteria. Infusion of oyster mushrooms baglog waste was mixed with 1% of molasses and was poured into soil obtained from the pepper plant roots. The concentrations used were 10%, 20%, 30% and 50%. Population of phytonematode, rhizobacteria, proteolytic bacteria, and group of fluorescence bacteria were calculated before and 7 days after treatment. Results showed that the populations of R. similis and Meloidogyne spp. in the soil poured with the influsion of oyster mushroom baglog waste decreased by 29.11% (R. similis) and 24.61% (Meloidogyne spp.), compared to the before and control treatments. The suppression of nematode population was found to be the highest in the influsion treatment at concentration of 50%. Overall, treatment of all concentrations succeeded to increase the population of rhizobacteria, proteolytic bacteria, and group of fluorescence bacteria in soil. Moreover, the highest increase was found in soil treated with concentration of 50%. This study provided new information that the infusion application of oyster mushrooms baglog waste enriched with molasses had the potential to increase the population of rhizobacteria and suppress the amount of pathogens R. similis and Meloidogyne spp.